Effects of blocking estradiol during impulsive choice and timing in female rats - Panfil, Kelsey (Kansas State University, 2020)
Previous research showed that female rats made more self-controlled choices and were more accurate and precise timing short delays during the proestrus phase of the estrous cycle (cycle of sexual fertility in rodents), which is when estradiol levels are highest compared to the other phases of the estrous cycle. The same pattern of decision making has occurred in human females based on self-reported menstrual cycles as well. These results suggest that estradiol may influence decision making in rats and humans. To test this hypothesis, rats received 0 mg/kg and 1 mg/kg of an estradiol antagonist before completing an impulsive choice task with timing assessments for multiple sessions. Overall, rats did not complete all trials, possibly due to satiety within the sessions, and the delay length and order of delays presented in the choice task may have negatively influenced decision-making above and beyond the effects of estrous cycle. On 0 mg/kg, rats in estrus made the most self-controlled choices, but there were no differences in self- controlled choices across estrous phases between 0 and 1 mg/kg. This suggests that natural increases in progesterone may result in increased self-control and estradiol may not reliably influence impulsive choice. However, blocking estradiol did affect temporal perception, although not in a systematic manner. The length of the timing interval and the reward values associated with each delay may have interacted with estradiol’s effects on temporal perception. In sum, estrous cycle effects on decision-making and timing may be mediated by delay length, delay order, and associated reward values.
Keywords: impulsive choice; timing; estradiol; decision making; rats